Crisis Between Spiritism and Psychology in Argentina: The Case of Parapsychology (1948-1955) (Revista de Psicología, 2024)
In the mid-forties, Argentine spiritualism faced a crisis in the context of cultural changes where they incepted parapsychology as a valid area of inquiry within the emerging psychology as a science. The fifties represented a transformation of the intellectual field for the so-called “conjectural sciences” and a form of psychologization of spiritualism. In fact, the appropriation of test results from J.B. Rhine in the United States proved useful to spiritualists. However, in the late 1940s an enthusiasm arose among mathematicians to learn about Rhine's statistical procedures and to test his hypothesis. In 1953, the Argentine Institute of Parapsychology (AIP) was created, whose activity was fruitful in the context of the nascent academization of the psychology because it began a process of demarcation that sought to purify parapsychology towards a position less contaminated by spiritist beliefs, in favor of the application of Rhine-oriented statistical procedures.
Keywords: Spiritualism; Parapsychology; J.B. Rhine; Statistics; Mediums